BEBERAPA FAKTOR YANG BERDAMPAK PADA PERBEDAAN AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BEJ) - Prabandari, Jeane Deart Meity; Rustiana, Rustiana (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2007)
This study examines the factors are impact on differences of audit delay in the financing firms that l isted at Jakarta Stock Exchange (JSE). These factors are total revenue, debt to assets ratio, gains or losses, audit opinion, and characteristic’s of accounting firms. Audit delay is measured as the length from the date of the project year-end to the date audit submits the annual report to BAPEPAM. Four hypotheses were tested by independent t-test or ANOVA. The study based on a sample of 111 the financial companies listed at JSE in year ended 2002 unti l 2004. There were differences of audit delay in total revenue and profit or loss announcement. But, no differences of audit delay in audit opinion and characteristic's accounting firm.Keywords: audit delay, total revenue, debt to seets ratio, audit opinion and characteristic's accounting firms